The Diagnostic and Immunotherapeutic Value of CD248 in Renal Cell Carcinoma - Zhang, Keying; Xu, Chao; Liu, Shaojie; Jiang, Yao; Zhao, Xiaolong; Ma, Shanjin; Li, Yu; Yang, Fa; Wang, Yan; Meng, Ping; Shi, Changhong; Han, Donghui; et al. (Frontiers in Oncology, 2021)
Background: Renal cell carcinoma (RCC) is the most common malignancy in urinary system. Despite substantial improvements in available treatments, survival outcome of advanced RCC is unsatisfied. Identifying novel biomarker to assist early diagnosis and screen immunotherapy sensitive patients would be beneficial. CD248 is a promising candidate that deserves to be investigated. Methods: The Cancer Genome Atlas (TCGA) dataset and clinical specimen were adopted to analyze CD248 expression between normal and tumor tissues. Univariate and multivariate Cox regression analysis was employed to identify independent prognostic factors and construct a CD248-based prognostic signature. The correlation among present signature, tumor infiltrating immune cells, tumor mutation burden (TMB), and immunomodulatory molecules were evaluated. Weighted gene co-expression network analysis (WGCNA), enrichment analysis, and miRNA correlation analysis was performed to explore the underlying mechanism of CD248 in RCC progression. Results: CD248 overexpressed in RCC was related with a poor prognosis, and CD248-based prognostic signature could precisely stratify RCC patients with different survival outcomes regardless of training or testing cohort. Present signature could reflect immunosuppressive landscape of RCC (i.e. increased regulatory T cells infiltration and upregulated immune checkpoints), which accompanied with deteriorated clinicopathologic indexes. TMB and immunostimulatory molecules expression also increased with the risk score generated from present signature. CD248 co-expressed gene sets were identified through WGCNA algorithm, and several immunosuppressive Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were significantly enriched. The result of CD248-correlated miRNA further emphasized the importance of CD248 in RCC. Conclusion: CD248 is a valuable biomarker to improve diagnostic and therapeutic efficiency of RCC. Immunosuppressive effect of CD248 co-expressed genes may provide insight for present study, and miRNA would help to reveal the mechanism of CD248 expressive regulation.